Blame the Switchman? Russian Railways Restructuring After Ten Years - Russell Pittman (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2011)
The Russian economy relies on the Russian freight railways to an extraordinary degree. In 2001, after years of debate, the Russian government adopted an ambitious plan to transform this vertically integrated, government owned monopoly into a system that would rely more on private investment and competition and less on government ownership and regulation. This paper examines the state of the industry after ten years of reforms, with a focus on competition, tariffs, and private sector participation. Much remains to be decided, in particular the question of whether Russia will settle on its own unique model of railways restructuring or will move in the direction of one of the three standard models seen in other countries: vertical separation as in the UK and Sweden, third party access as in Germany and France, or horizontal separation, as in the US, Canada, and Mexico.
Keywords: 330; freight railways; restructuring; competition; Russian Federation; vertical separation; third party access; horizontal separation